Efeitos da Endotelina 1 na infecção, in vitro, de cardiomiócitos com a cepa Y de Trypanosoma cruzi - Fabio Henrique Guimarães Braga (2011)
Endothelin-1 (ET-1) plays an important role in regulation of cardiovascular functions, and has been implicated in cardiovascular diseases, such as hypertension, atherosclerosis, and heart failure, particularly in the inflammatory process occurring during these pathologies. Several cellular types are able to secrete ET-1, among them cardiomyocytes. Patients with chagasic cardiomyopathy present elevated serum levels of ET-1 and evidences point to a role of endothelins in the pathogenesis of the disease. During experimental Trypanosoma cruzi infection high serum levels of ET-1 are also described as well as an altered expression of its receptors. Dual blockade of ETA and ETB receptors in rats provokes an elevation of parasitemia and a shift of the inflammatory profile in cardiac tissue. In vitro, the dual blockade causes an augment of intracellular parasites in macrophages. In this study, we evaluated the effects of treatment with ET-1 and bosentan, a dual antagonist of ET-1 receptors, on cardiomyocytes infected in vitro with Y strain of T. cruzi. Levels of NGF were elevated in the supernatants of control cultures 48 hours after treatments with ET-1 or with bosentan followed by ET-1. Higher levels of ET-1 were detected after bosentan treatment and after double treatment, but with higher levels after bosentan treatment. Cytokines were not detected in the supernatants of control cultures, except for TNF-, that was detected after double treatment. The infection provoked an elevation of NGF levels in the supernatants of all groups evaluated, with higher levels after bosentan or double treatment. Similar kinetics was seen for ET-1 levels. NO was detected only in infected cultures, with higher levels after 48 hours of infection. TNF- was detected only in cultures with 48 hours of infection, except after double treatment, when the cytokine was detectable in both times, 24 and 48 hours of infection. Concerning IL-10, the treatment with ET-1 elevated their levels 24 hours after infection. The double treatment provoked a higher level of TNF- and IL-10 in both, control and infected cultures. Double treatment also induced higher percentage of infected cells and higher infection rate. Altogether these results reinforce the role of ET-1 in the response of cardiomyocytes to T. cruzi infection.